The Effect of the Flipped Classroom Model on Elementary Students’ Science Literacy - Pit Syahni; Ahmad Khoiri; Joni Albar (Chatra: Jurnal Pendidikan dan Pengajaran, 2026)
This study examines students’ science literacy through the implementation of the flipped classroom model in an elementary school context. The research is grounded in the persistent challenge of low science literacy, often associated with limited student engagement and teacher-centered instructional practices. Positioned within a quantitative framework, this study employs a pre-experimental one-group pretest–posttest design to analyze changes in students’ performance before and after the intervention. The participants consisted of 15 fifth-grade students at SDN 20 Tanjung Keramat, selected using a saturated sampling technique. Data were collected using a science literacy test adapted from PISA indicators and analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results indicate a consistent increase in students’ scores, with all participants demonstrating improvement and no decline observed. Statistical analysis reveals a significant difference between pretest and posttest results, suggesting that the flipped classroom model is associated with enhanced science literacy. These findings highlight the potential of structured active learning environments in supporting deeper conceptual understanding. However, the use of a pre-experimental design and a small sample size limits the generalizability of the results. Future research is recommended to employ more rigorous designs and broader samples. Penelitian ini bertujuan untuk menganalisis kemampuan literasi sains siswa melalui penerapan model pembelajaran flipped classroom pada konteks sekolah dasar. Penelitian ini dilatarbelakangi oleh rendahnya literasi sains siswa yang sering dikaitkan dengan rendahnya keterlibatan belajar serta dominasi pembelajaran berpusat pada guru. Penelitian ini menggunakan pendekatan kuantitatif dengan desain pre-experimental one-group pretest–posttest untuk mengidentifikasi perubahan kemampuan siswa sebelum dan sesudah perlakuan. Subjek penelitian berjumlah 15 siswa kelas V di SDN 20 Tanjung Keramat yang dipilih menggunakan teknik sampling jenuh. Data dikumpulkan melalui tes literasi sains yang disusun berdasarkan indikator PISA dan dianalisis menggunakan statistik deskriptif serta uji Wilcoxon Signed-Rank. Hasil penelitian menunjukkan adanya peningkatan skor pada seluruh siswa tanpa adanya penurunan nilai. Analisis statistik juga menunjukkan perbedaan yang signifikan antara hasil pretest dan posttest, yang mengindikasikan bahwa penerapan flipped classroom berkaitan dengan peningkatan literasi sains siswa. Temuan ini menunjukkan pentingnya pembelajaran aktif yang terstruktur dalam mendukung pemahaman konsep secara lebih mendalam. Namun demikian, penggunaan desain pre-experimental dan ukuran sampel yang terbatas menjadi keterbatasan dalam penelitian ini. Penelitian selanjutnya disarankan menggunakan desain yang lebih kuat dan cakupan sampel yang lebih luas.